2013
DOI: 10.1111/eci.12061
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐induced acute kidney injury following PCI

Abstract: Background Coronary revascularization using percutaneous coronary intervention (PCI) is one of the major treatments for patients with stable coronary artery disease (CAD), with approximately 1.5 million patients undergoing PCI in the United States and Europe every year. An important neglected complication of PCI is contrast-induced acute kidney injury (CI-AKI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 100 publications
1
44
0
Order By: Relevance
“…Patients with CHD combined with hyperuricemia have higher incidence of myocardial infarction. The global number of cardiac surgeries or PCI each year is approximately 2 million [28, 29] and one of the most common and serious post-operative complications is AKI. A current meta analysis found that the incidence of AKI after cardiac surgery was 22.3% around the world (95% CI 19.8-25.1) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CHD combined with hyperuricemia have higher incidence of myocardial infarction. The global number of cardiac surgeries or PCI each year is approximately 2 million [28, 29] and one of the most common and serious post-operative complications is AKI. A current meta analysis found that the incidence of AKI after cardiac surgery was 22.3% around the world (95% CI 19.8-25.1) [2].…”
Section: Discussionmentioning
confidence: 99%
“…This is termed 'contrast-induced AKI (CI-AKI)'. 5, [21][22][23] There is a concern about the risk of CI-AKI for patients undergoing coronary angiography and primary PCI for AMI. In the present study, however, both emergency angiography and primary PCI were not associated with AKI in AMI patients.…”
Section: Incidence Of Aki In Ami Patientsmentioning
confidence: 99%
“…CIN has become the third leading cause of hospital acquired acute renal failure [2]. The risk factors for CIN are pre-existing renal failure, presence of diabetes mellitus (DM), anemia, dehydration, congestive heart failure, advanced age, gender, excess volume of contrast medium used, and simultaneous usage of nephrotoxic drugs [3].…”
mentioning
confidence: 99%